Efficacy analysis of serum ferritin, Hcy, CRP combined with fat ultrasound parameters in predicting metabolic dysfunction-associated steatotic liver disease - Yu, Haitao; Ma, Liju; Chen, Yuxiang; Liu, Juan; Li, Linjian; Yang, Zhifang; Xu, Jing; Guo, Bei (Frontiers in Medicine, 2025)
ObjectiveTo investigate the efficacy of combined prediction of serum ferritin, Hcy, CRP, and fat ultrasound parameters in metabolic dysfunction-associated steatotic liver disease (MASLD).MethodsOne hundred and two MASLD patients admitted to our hospital from November, 2021 to November, 2023 were selected as the MASLD group, and 106 healthy subjects were selected as healthy group on the basis of the principle of 1:1, and the healthy group was not accompanied by any basic diseases. The differences in demographic data, medical records and biochemical indicators between the MASLD group and the healthy group were analyzed by single factor analysis. The suspected influencing factors of MASLD were screened by single factor analysis. Apply multivariate Logistic regression to examine the independent predictors of MASLD. Employ ROC curve to anticipate the effect of single and combined indicators.ResultsSingle factor analysis revealed that the SF, Hcy, CRP, and CAP level in MASLD group were significantly higher than healthy control group (p < 0.05). Multivariate Logistic analysis displayed that SF, Hcy, CRP, and CAP were independent predictors of alcoholic fatty liver disease (p < 0.05). ROC curve displayed that the area under the curve of the joint prediction of SF, Hcy, CRP, and CAP was 0.941, which was significantly higher than the area of SF, Hcy, CRP, and CAP alone.ConclusionThe combined application of serum SF, Hcy, CRP, and CAP has a high predictive efficiency for MASLD, which can be employed as an important reference indicator for early clinical diagnosis and intervention.